Big Catch, Undecided Risks: Perspectives of Risk, Reward, and Trade‐Offs in Alaska's Salmon Enhancement Program. (9th November 2022) - Harrison, Hannah L.; Gould, Julie Grønsleth
Abstract: Alaska's salmon enhancement program plays an important and substantial role in commercial fishing harvests situated around the Gulf of Alaska, Prince William Sound, and Southeast Alaska. In recent years, discussions about the ecological impacts of the enhancement program have emerged in the media, the Alaska Board of Fisheries, and other public discourses. These discussions have illuminated tension within Alaskan society about the role and impacts of hatcheries in fisheries and coastal communities. This study uses qualitative methods to identify key themes that underlie those tensions within Alaska Board of Fisheries public comments and private discourses. We found that issues raised in public comment formats were limited to four key themes, whereas interviews revealed those same themes as well as a broader and more nuanced cross section of themes, both critical and complimentary of the enhancement program. We discuss these themes within the context of enhancement policy and ongoing research into wild–hatchery salmon interactions, both of which pose certain constraints about how trade‐offs between social, ecological, and economic valuation of the enhancement program can be made. We suggest a road map of four steps for action to help avoid potential societal conflict in the future: (1) establish a process to incorporate socio‐cultural dimensions of hatcheries and stocking into enhancement program decision making; (2) better define "adverse impacts" within enhancement policy; (3) link current and future research findings to decision‐making processes and policy implications; and (4) plan for the future(s) through scenario development work aimed at identifying the ecological and societal impacts of different enhancement policy changes, such as drawing down, scaling up, or otherwise altering existing stocking practices.